Fetal loss in pregnant rhesus macaques infected with high-dose African-lineage Zika virus. - Lauren E Raasch; Keisuke Yamamoto; Christina M Newman; Jenna R Rosinski; Phoenix M Shepherd; Elaina Razo; Chelsea M Crooks; Mason I Bliss; Meghan E Breitbach; Emily L Sneed; Andrea M Weiler; Xiankun Zeng; et al. (Public Library of Science (PLoS), 2022)
Countermeasures against Zika virus (ZIKV), including vaccines, are frequently tested in nonhuman primates (NHP). Macaque models are important for understanding how ZIKV infections impact human pregnancy due to similarities in placental development. The lack of consistent adverse pregnancy outcomes in ZIKV-affected pregnancies poses a challenge in macaque studies where group sizes are often small (4-8 animals). Studies in small animal models suggest that African-lineage Zika viruses can cause more frequent and severe fetal outcomes. No adverse outcomes were observed in macaques exposed to 1x104 PFU (low dose) of African-lineage ZIKV at gestational day (GD) 45. Here, we exposed eight pregnant rhesus macaques to 1x108 PFU (high dose) of African-lineage ZIKV at GD 45 to test the hypothesis that adverse pregnancy outcomes are dose-dependent. Three of eight pregnancies ended prematurely with fetal death. ZIKV was detected in both fetal and placental tissues from all cases of early fetal loss. Further refinements of this exposure system (e.g., varying the dose and timing of infection) could lead to an even more consistent, unambiguous fetal loss phenotype for assessing ZIKV countermeasures in pregnancy. These data demonstrate that high-dose exposure to African-lineage ZIKV causes pregnancy loss in macaques and also suggest that ZIKV-induced first trimester pregnancy loss could be strain-specific.